Digital Penetration of Halal Cosmetic Business in Indonesia During 4.0 Revolution - Purwanto, Purwanto; Abdurachman, Fatimah Azzahra; Fadhila, Sarah Nurul; Fajrin, Selaraswati (LPPM Universitas Terbuka, 2022)
The Government launched the Roadmap of “Making Indonesia 4.0” as one of the strategies for implementing industry 4.0 in Indonesia encourages the development of various industries, including E-Commerce. Many companies also apply this technology, one of which is by utilizing digital marketing. This study aims to see the effect of digitization on the halal industry in Indonesia, especially in the field of halal cosmetics. The method used in this research is literature review with the topic of digitization that focuses on digital marketing. The object of this research is Wardah Cosmetics. From this research shows that the digitization carried out by Wardah Cosmetics in the form of digital marketing with the use of media is proven to have an effect on increasing brand awareness and digital sales of its products. It can be argued that revolution 4.0 or digitalization is very significant for economic growth in Indonesia. In addition, digital media can increase business efficiency and profits as well as as a media da'wah for the halal industry. Further research is needed regarding the application of digitization in the Islamic economy to be an important part of the Indonesian Sharia Economics Master Plan (MEKSI).